Remimazolam Protects Against LPS-Induced Endotoxicity Improving Survival of Endotoxemia Mice - Xiaolei Liu (Frontiers Media S.A., 2021)
Remimazolam is a new benzodiazepine of sedative drugs with an ultra-short-acting anesthetic effect, commonly used for critically ill patients (especially septic patients) in intensive care units (ICUs). Although some anesthetics have been reported to show certain anti-inflammatory effects, the role of remimazolam in inflammation is still remained unknown. Here, we studied the effects of remimazolam on macrophage in response to LPS both in vivo and in vitro. Interestingly, compared with LPS treatment group, remimazolam remarkably improved survival rate of endotoxemia mice and decreased the release of LPS-induced inflammatory mediators (such as TNF-α, IL-6, and IL-1β). We further found that remimazolam not only inhibited the activation of MAPK signal pathway at 15 min after LPS treatment but also disturbed Rab5a related TLR4 expression at cell surface in response to LPS at a later time. Such evidence suggests that remimazolam might be beneficial to septic patients who are suffering from uncontrolled inflammatory responses.